Enhancing Understanding Through Conversation in English Language Learning Among University Students - Nisa, Naila Halwatun; Asti, Dwi; Pulungan, Gyan Suhaimi; Lubis, Yani (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
The ability to comprehend English functionally remains a challenge for many university students in Indonesia. Although students often acquire theoretical knowledge such as grammar and vocabulary, they frequently struggle with understanding real-life conversational contexts. This study aims to examine how the conversation approach helps build students’ comprehension in English language learning. Using a qualitative method with a case study approach, data were collected through observation, interviews, and documentation from final-year students at a university. The findings reveal that active engagement in conversation activities significantly improves students’ contextual understanding, self-confidence, and critical thinking skills. These results are supported by key learning theories such as Communicative Language Teaching (Savignon), Affective Filter Hypothesis (Krashen), Socio-Cultural Theory (Vygotsky), and Experiential Learning Theory (Kolb). Moreover, conversation fosters a more humanistic, participatory, and contextually relevant learning environment. Therefore, integrating conversation methods into English instruction in higher education is highly recommended as a strategy to enhance deep and applicable language comprehension.